Principal's Leadership Role in Developing Education Quality Culture - Ari Wibowo Sembiring; Budi Budi (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
This study examines the role of principal leadership in fostering a culture of quality education at SMP IT Mutiara. This study adopts a descriptive qualitative approach to explore the transformational leadership strategies implemented by the principal in building a conducive learning environment through data collection methods such as observation, interviews, and notes. The findings of the study indicate that the principal plays a strategic role in shaping a culture of quality education through various integrated strategies, including mentoring and developing teacher professionalism, and encouraging active participation from all school members. Despite facing challenges such as rejection from senior teachers towards new teaching methods, budget constraints, and the balance between academic achievement and Islamic character development, the principal overcomes these obstacles through his visionary, communicative, and focused leadership. The positive impact of developing a culture of quality education can be seen from the increasing quality of graduates accepted at the selected school, the increasing professionalism of teachers, and the high achievement of students in both academic and non-academic fields. This study confirms that the leadership of the principal is not merely administrative, but is a driving force for educational transformation that drives all departments in the school to provide the best educational services.